Post-myocardial infarction fibrosis: Pathophysiology, examination, and intervention - Yin, Xiaoying; Yin, Xinxin; Pan, Xin; Zhang, Jingyu; Fan, Xinhui; Li, Jiaxin; Zhai, Xiaoxuan; Jiang, Lijun; Hao, Panpan; Wang, Jiali; Chen, Yuguo (Frontiers in Pharmacology, 2023)
Cardiac fibrosis plays an indispensable role in cardiac tissue homeostasis and repair after myocardial infarction (MI). The cardiac fibroblast-to-myofibroblast differentiation and extracellular matrix collagen deposition are the hallmarks of cardiac fibrosis, which are modulated by multiple signaling pathways and various types of cells in time-dependent manners. Our understanding of the development of cardiac fibrosis after MI has evolved in basic and clinical researches, and the regulation of fibrotic remodeling may facilitate novel diagnostic and therapeutic strategies, and finally improve outcomes. Here, we aim to elaborate pathophysiology, examination and intervention of cardiac fibrosis after MI.